(3fNHI GdTGQH hoYLGdI GdQGcHs - (3eLghds ((3eMeO Hf eMehO Hf GdMSf GdSeQbfOj s)
(3ChdgG (B:s
(3hHYO, abO gR eYGWaj QHGYjGJ eQJ HSeYj hMdJ aj ePGb WHYj s
(3BNQgG (B:s
(3oQeJ HgG GdCYJPGQ Yf GdEWGdI, hGeJOGO GdfaS aj GdbUjOI hGdQSGdI NhakG ef GdedGdI JeJ GdQYjGJ HJeGegG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HChdgG JedcGJ CbOegG SfI (B957(3g```s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B133 s
Keywords: (3GdCOHs